Exploring the Relationship Between Academic Supervision and Pedagogical Competence in Secondary Education: A Quantitative Study in Cilegon - Kiki Maullidina; Cucu Atikah; Rudi Haryadi (STAI Hubbulwathan Duri, 2025)
Teachers’ pedagogical competence is a key determinant of instructional quality and student-centered learning. Academic supervision is widely recognized as a professional support mechanism to enhance teachers’ instructional practices; however, empirical evidence from localized secondary school contexts in Indonesia remains limited. This study examines the relationship between academic supervision and pedagogical competence among senior high school teachers in Cilegon City. A quantitative correlational design was employed involving 30 senior high school teachers selected through simple random sampling. Data were collected using validated and reliable questionnaires measuring academic supervision and pedagogical competence. Pearson product–moment correlation analysis was conducted using SPSS after confirming the assumptions of normality and linearity. The findings reveal a strong and statistically significant positive relationship between academic supervision and teachers’ pedagogical competence (r = 0.836, p = 0.001), indicating that teachers who perceive supervision as structured and developmental tend to report higher levels of pedagogical competence. The results suggest that academic supervision plays an important role in supporting teachers’ pedagogical development, particularly when implemented systematically and reflectively. These findings align with the objectives of Kurikulum Merdeka and current national education policies emphasizing teacher professionalism and continuous improvement. Despite limitations related to sample size and self-reported data, this study provides contextualized evidence supporting the strengthening of academic supervision practices. Future research should employ longitudinal and mixed-method approaches to further explore the mechanisms through which supervision contributes to sustained pedagogical improvement.